(untitled) (Academicia Globe: Inderscience Research, 2022)
The organization of the information and technical base on the basis of the logistics system, the collection and separation of information play a key role in solving the strategic and tactical tasks required for management. The nature of the information and its quality will have a significant impact on the outcome of decisions.